Pengampunan Pajak, Prinsip Keadilan Berdasarkan Undang-Undang No. 11 Tahun 2016 Tentang Pengampunan Pajak - Faradiba Mutiara Dewi; Weny Almoravid Dungga; Waode Mustika (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this research is to find out how the regulations regarding tax amnesty in Indonesia are based on Law no. 11 of 2016 concerning Tax Forgiveness and to find out how to implement Tax Forgiveness in Indonesia so that it meets the Principles of Justice. The research method used is normative legal research. The research results obtained regarding the fulfillment of the principles of justice in the implementation of tax amnesty in Indonesia based on Law no. 11 of 2016 concerning Tax Amnesty, namely that it has fulfilled the principle of justice, seen from the number of tax payments received and the number of taxpayers who comply to report their taxes. The increase in taxpayers who comply through the implementation of tax amnesty will also increase taxpayers reporting and correcting notification letters regarding their assets as well as taxpayer awareness of tax amnesty which has an important role in increasing taxpayer compliance.